Otimização do potencial turístico do Vale do Jiquiriçá através da aplicação do modelo de Cluster - Simões, Polyana Almeida (2006)
To investigate the possibility of a regional touristy potential optimization leads to the investigation of some great studies about the economic development thought, which supplies the building of multiorganizational models focused on tourism regional development, trying to understand the sense of industrial and service agglomerations within a sustainable and endogenous context. The stress of this critical evaluation was based on suppositions described by Michael Porter's economic cluster theory, pointing out questions, such as competitivety and cooperation between companies that provided a higher understanding about private, public, non-governmental and society interactive linkages, and propitiating a local and sustainable development. The analysis and conception of four cooperative management models, including the cluster one, also considered its projection to tourism activity and to political, social and economical outlook from Laje, Mutuípe, Jiquiriçá and Ubaíra, cities situated at Jiquiriçá Valley in Bahia. The main goal that justify this dissertation was to draw an analysis of a touristy cluster's arrangement viability, geographically located inside the boundaries of the cities taken into consideration and, from this analysis on, finding out if the application of this model as a support to the touristy potential optimization and to the local shared administration, actually exists or if it can still become a reality. The clusters organizational dynamic would help on the elaboration of deliberative policies and strategic procedures able to change the touristy features at Jiquiriçá Valley. The experience of the Jiquiriçá Valley Inter-city Organization (CIVJ) confirms, in a distinct level, the existence of an interaction between actors and also of a linkage with the local society. However, when the subject matter is tourism, the cities show some obstacles on planning processes and on connected actions and projects accomplishment. The research denoted a huge potential to tourism activity that is already experienced indiscriminately and inceptively. Because of the diagnostic, the developed study could confirm the lack of financial and administration resources in order to invest on basic structures, including roads and tourism equipments. The indications of a management practiced through a possible establishment of a regional cluster seem to be the best solution to the Jiquiriçá Valley's consolidation as a competitive touristy destiny.